Da'wah Communication and Inclusive Campaign Strategies in the 2024 Semarang Mayoral Election - Novia Maria Ulfah; Abu Hapsin; Puji Lestari; Moch Parmudi; Wahid Abdulrahman (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2026)
Semarang is sociologically populated by a Muslim majority, but geopolitically, historically, it is known as a strong base for the nationalist group (PDIP). This unique contradiction demands that political actors formulate adaptive campaign strategies for the 2024 Semarang mayoral election. This study aims to analyze the winning strategies implemented by candidates to capture Muslim voters without negating the nationalist cultural identity of Semarang residents. This study aims to analyze the campaign methods and strategies that significantly influenced the victory in the 2024 local election in Semarang City. This research employs a qualitative approach with Semarang City as the research locus. Data were collected through interviews, observation, and documentation. The collected data were analyzed using the interactive analysis model proposed by Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the victory of Agustina-Iswar was influenced by several key factors, including the strength of political party machinery, the candidate’s personal figure and political charisma, support from volunteers and the community, direct engagement activities with the public such as market visits, group exercise activities, and visits to micro, small, and medium enterprises, outreach and relationship-building with Islamic religious leaders (kiai and ulama) in Semarang City, as well as pro-people policy programs, such as the provision of operational assistance amounting to IDR 25 million per neighborhood unit (RT) per year.